Aplicação do profile uml marte na modelagem de serviços de protocolos de comunicação de tempo real - Silva, Diego Alves da (2014)
In the context of the Internet and distributed systems, there is the application of new technologies and devices to enhance the support for mobility, security, quality of service and multicast. There are many approaches to the modeling of distributed systems to behavior validation. In addition, approaches which have support for modeling of realtime requirements are difficult to read, interpret and by creation of human models. In this way, this work aims to present an approach to modeling communication protocols using the MARTE/UML profile that supports the requirements of real-time and having a streamlined reading. In this work, two modeling approaches for communication protocols of the Internet architecture Entity Title Architecture (ETArch) were created. An approach using pure UML and the second the profile MARTE. In addition, a parser for VSL language model that accounts for the expression of real time constraints of the models of the second approach was created. In order to ensure the future applicability of the proposed approach, a questionnaire based on the Technology Acceptance Model was performed. According to this model, the proposed approach was positive for most users. Compared to other approaches, the one proposed in this work is advantageous by allowing both visual modeling as an algebraic model for the representation of constraints, allowing a mathematical validation.